√50 + √242 - √2
= √5·5·2 + √11·11·2 -√2
= 5√2 + 11√2 - √2
= 16√2 - √2
= 15√2
Answer:
27
Step-by-step explanation:
Let the middle number be x.
(x - 1)(x)(x + 1) = 21,924
You can solve that equation, or you can use logic.
The 3 numbers are going to be close to the cubic root of 21,924.
cubic root of 21,924 = 27.988 or approx 28.
Try 27, 28, 29
27 * 28 * 29 = 21,924
Answer: 27
You factor the numerator and denominator and cancel the common factors. So maybe that should help you
Answer:
• x = -4, x = 0, x = 1
Step-by-step explanation:
x is a factor of all terms, so x=0 is a zero. (Eliminates choices 1 and 5.)
The sum of coefficients is 0, so x=1 is a zero. (Eliminates choices 3 and 4.)
Reversing the sign of the odd-degree terms gives signs of -++, so there is one sign change, hence one negative real root (by Descartes' rule of signs). This confirms choice 2 as the answer.
___
Of course, your graphing calculator can answer this almost as quickly.
3=−(−y+6)
Simplify:
3=−(−y+6)
3=y+−6(Distribute)
3=y−6
Flip the equation.
y−6=3
Add 6 to both sides.
y−6+6=3+6
y=9